O rei que esmorece e a rainha sanhuda - Inês Olaia (Medievalista)
The 1383-1385 dynastic crisis has been studied by generations of historians. This article aims to contribute to the debate through a florescent historiographical field that does not seem to have been used to analyse the main narrative of the events, written by Fernão Lopes: the History of Emotions. We will study the emotional palette expressed by the kingdom’s official chronicler and perceived by his Portuguese medieval readers in an attempt to understand how it sustains the rise to the throne of the Master of the Military Order of Avis. The work is structured around three royal couples and the emotions expressed and provoked by them: Leonor Teles and D. Fernando as the bad example because of their emotional imbalance that drives the kingdom to chaos and the inadequacy of the roles they play to what is expected from them; Juan I of Castile and Beatriz of Portugal who arise despair and negative emotions; João I and Philippa of Lancaster who help to restore normality by their balanced and positive performance. In each of these cases the first element mentioned is dominant on the references.